The GeoGebra-Aided Visualization of Geometric Concepts in Bugisnese Traditional Musical Instruments Gendrang and Pui-pui - Hafis, Hafis; Ferdiani, Rosita Dwi; Suastika, I Ketut (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2025)
This study lies in the need to bridge school mathematics with local cultural heritage by emphasizing the relevance of the ethnomathematics framework in promoting contextual learning. Traditional musical instruments, such as Gendrang (Bugisnese drums) and Pui-pui (Bugisnese flutes), serve as cultural artifacts that can be explored through the lens of three-dimensional geometry. However, the integration of these cultural elements into mathematics education remains underexplored. This research aims to identify and model geometric concepts embedded in the two Bugisnese traditional musical instruments using GeoGebra as a visualization tool. Employing a qualitative ethnographic approach, data were collected through observation, interviews, and documentation. The analysis involved identifying geometric shapes in the instruments and constructing mathematical models in GeoGebra. Findings reveal that Gendrang corresponds to a cylindrical shape, while Pui-pui resembles a conical shape. The volumes of both instruments were calculated using the concept of solids of revolution, and visualized interactively. The study concludes that the exploration of ethnomathematics through Bugisnese traditional musical instruments, supported by dynamic visualization in GeoGebra, enhances students’ understanding of three-dimensional geometry, fosters cultural appreciation, and reinforces the contextual relevance of mathematics in local traditions.